Yrittäjyyskasvattaja : ammattikorkeakoulun hallinnon ja kaupan alan opettajien näkemykset itsestään ja työstään yrittäjyyskasvattajana - Paajanen, Pekka (2001)
The aim of the study was to examine what kind of views do the teachers at the polytechnic level, in the field of business and administration, have of themselves and their work as an entrepreneurship educator. The research questions were: 1) how is the concept entrepreneurship perceived among teachers?, 2) what are teachers' attitudes towards the entrepreneurship?, 3) to what extent will there be entrepreneurial behavior among the teachers and their organizations, according to teachers?, 4) what kind of conceptions do the teachers have of the best learning methods from entrepreurship education's point of view? and 5) what are the learning methods the teachers are using? In the theoretical part of the study, framework, objects analysed were the concepts of entrepreneurship, entrepreneurship education, education and learning, learning methods and affective field, i.e. philosophy of life, values, attitudes and motivation and connection between them and entrepreneurship. The ideal model of the entrepreneurship educator was presented as a synthesis of the conceptual analysis. The empirical part of the study consisted of a questionnaire designed for the teachers at the polytechnic level, in the field of business and administration. Questionnaires were sent to 575 teachers in randomly selected business schools all over Finland. Acceptable replies were received from 218 teachers. The return rate was 37.9 per cent. The statistical methods used were descriptive statistics (frequencies, means and standard deviations), correlations and factor analyses. T-tests and variance analyses were used testing statistically significant differences. Generally speaking respondents' views of themselves as an entrepreneurship educator were quite positive. In general, the concept of entrepreneurship was recognized and understood as a wide and multidimensional phenomen. According to respondents, the concept of entrepreneurship emphasizes activity and risk-taking, persistence, owner-entrepreneurship, work commitment, economic values and results, innovativeness, managership, willingness to achieve and selfishness. The dimensions of attitudes towards entrepreneurship were grouped into five categories: attitudes towards market economy, SME's, entrepreneurs, establishing an enterprise and work. The attitudes of the teachers towards the entrepreneurship were quite positive. Attitudes were most positive towards the SME's and the work. The views of the entrepreneur's behavior were very idealistic. Nine factors were identified and they were named as follows: independence and self-confidence, autonomy, willingness to develop, risk-taking and willingness to compete, managing one's own life, egoism, change resistance, need for security and bureaucracy minded. Teachers' views of entrepreneur's behavior were clearly more positive than their conceptions of themselves and their organizations. In general respondents recognized themselves more positive comparing their organizations for positive factors' part. According to respondents useful methods from entrepreneurship education's point of view were the ones with focus on action-orientation, problem-orientation, real life experience and collaboration with business life. On the other hand the most commonly used methods were traditional learning methods in class room context without collaboration with enterprises. On the whole differences between the useful methods and the use of methods were quite large and significant.